In vivo nanoparticle imaging of innate immune cells can serve as a marker of disease severity in a model of multiple sclerosis - Kirschbaum, Klara; Sonner, Jana K.; Zeller, Matthias W.; Deumelandt, Katrin; Krüwel-Bode, Julia; Sharma, Rakesh; Krüwel, Thomas; Fischer, Manuel; Hoffmann, Angelika; Costa da Silva, Milene; Muckenthaler, Martina; Wick, Wolfgang; et al. (Proceedings of the National Academy of Sciences of the United States of America, 2016)
Innate immune cells play a key role in the pathogenesis of multiple sclerosis and experimental autoimmune encephalomyelitis (EAE). Current clinical imaging is restricted to visualizing secondary effects of inflammation, such as gliosis and blood-brain barrier disruption. Advanced molecular imaging, such as iron oxide nanoparticle imaging, can allow direct imaging of cellular and molecular activity, but the exact cell types that phagocytose nanoparticles in vivo and how phagocytic activity relates to disease severity is not well understood. In this study we used MRI to map inflammatory infiltrates using high-field MRI and fluorescently labeled cross-linked iron oxide nanoparticles for cell tracking. We confirmed nanoparticle uptake and MR detectability ex vivo. Using in vivo MRI, we identified extensive nanoparticle signal in the cerebellar white matter and circumscribed cortical gray matter lesions that developed during the disease course (4.6-fold increase of nanoparticle accumulation in EAE compared with healthy controls, P < 0.001). Nanoparticles showed good cellular specificity for innate immune cells in vivo, labeling activated microglia, infiltrating macrophages, and neutrophils, whereas there was only sparse uptake by adaptive immune cells. Importantly, nanoparticle signal correlated better with clinical disease than conventional gadolinium (Gd) imaging (r, 0.83 for nanoparticles vs. 0.71 for Gd-imaging, P < 0.001). We validated our approach using the Food and Drug Administration-approved iron oxide nanoparticle ferumoxytol. Our results show that noninvasive molecular imaging of innate immune responses can serve as an imaging biomarker of disease activity in autoimmune-mediated neuroinflammation with potential clinical applications in a wide range of inflammatory diseases.
Gesehen am 13.05.2020